Peer group influence on academic performance of selected secondary school students in Akinyele local government area,Ibadan, Oyo state (2021)
Peer groups play important roles in adolescents’ outcomes as a result of their significant influence in the social, psychological and educational development of students. However, its role in student performance has largely been under-reported and factors underlining this behavior among secondary students in Akinyele LGA have not been explored in recent literature. This study investigated the influence of peer group on the academic performance of secondary school students among secondary students in Akinyele Local Government Area of Oyo state The study adopted the exploratory descriptive rese arch design in eliciting information on the influence of peer groups on the academic performance of students in selected secondary schools. The main instrument used for the study was questionnaire. The data collected from the students were analyzed using frequency counts and simple percentage based on the 4-points scale. The study concludes that peer groups influence positively affect academic performance of secondary school students the underlining reinforcing factors include financial, emotional and social benefits of peer groups also. tacit and indirect parental support moderated the influence of these peer groups The government and ministry of education should ensure that, trained counselors are made available in all schools so as to provide preventive counseling Services and modify the behaviors of students who unfortunately influenced negatively by peers